Bioactive cell-derived matrices combined with polymer mesh scaffold for osteogenesis and bone healing - Kim, In Gul; Hwang, Mintai P.; Du, Ping; Ko, Jaehoon; Ha, Chul-won; Do, Sun Hee; Park, Kwideok (ELSEVIER SCI LTD, 2015)
Successful bone tissue engineering generally requires an osteoconductive scaffold that consists of extracellular matrix (ECM) to mimic the natural environment. In this study, we developed a PLGA/PLA-based mesh scaffold coated with cell-derived extracellular matrix (CDM) for the delivery of bone morphogenic protein (BMP-2), and assessed the capacity of this system to provide an osteogenic microenvironment. Decellularized ECM from human lung fibroblasts (hFDM) was coated onto the surface of the polymer mesh scaffolds, upon which heparin was then conjugated onto hFDM via EDC chemistry. BMP-2 was subsequently immobilized onto the mesh scaffolds via heparin, and released at a controlled rate. Human placenta-derived mesenchymal stem cells (hPMSCs) were cultured in such scaffolds and subjected to osteogenic differentiation for 28 days in vitro. The results showed that alkaline phosphatase (ALP) activity, mineralization, and osteogenic marker expression were significantly improved with hPMSCs cultured in the hFDM-coated mesh scaffolds compared to the control and fibronectin-coated ones. In addition, a mouse ectopic and rat calvarial bone defect model was used to examine the feasibility of current platform to induce osteogenesis as well as bone regeneration. All hFDM-coated mesh groups exhibited a significant increase of newly formed bone and in particular, hFDM-coated mesh scaffold loaded with a high dose of BMP-2 exhibited a nearly complete bone defect healing as confirmed via micro-CT and histological observation. This work proposes a great potency of using hFDM (biophysical) coupled with BMP-2 (biochemical) as a promising osteogenic microenvironment for bone tissue engineering applications. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: MESENCHYMAL STEM-CELLS; MULTI-LINEAGE DIFFERENTIATION; EXTRACELLULAR-MATRIX; MICROENVIRONMENT; VASCULARIZATION; MORPHOGENESIS; CONSTRUCTS; MIGRATION; CARTILAGE; STRENGTH